The knowledge management levels in the development of online courses - Natalia V. Dneprovskaya; Inessa V. Shevtsova (Открытое образование (Москва), 2017)
The knowledge management (KM) development was closely associated with e-learning from the beginning. E-learning is a part of the knowledge management tools, which is widely used in companies and universities for the knowledge dissemination. KM methods are used in the system of education management to solve problems of innovative development for educational institutions. The main goal of knowledge management is to support the innovative activities of lecturers and researchers. The development of elearning courses is an example of innovative activity at the university. Elearning course contains the results of scientific and methodical activities of the Faculty, and it is a ready-made innovative product of the university. The technology and methods of e-learning have already became an essential support tool for the training process at the leading universities in Russia and in the world. The scientific novelty of the research is to identify the KM levels in the development of e-learning courses.The paper shows KM levels in e-learning: individual, team, university, inter-university and global. There is a paradoxical situation in the academic environment. Many universities are willing to support free access to its educational content through the platform of open educational resources (OER), or massive open on-line courses (MOOC), however, the development of inter-university courses often is an initiative of self-organizing authors’ groups. The development of each KM level in the university is the basis for the complete work at a higher level. The determination of KM levels in the university allows to create a comprehensive strategy for e-learning, aimed at the creation of on-line courses and e-learning development, which is extremely important in the global information environment.